Assessing the Culture of Deliberation in Local Governance: Evidence from Four Municipalities in Kailali, Nepal - Shahi, Min Bahadur (Far Western Review, 2025)
This study critically examines deliberative practices within the executive bodies (karyapalika) of local governments in Nepal’s evolving federal governance system, drawing empirical insights from four municipalities in the Kailali district, Nepal. Following the promulgation of the 2015 Constitution and the enactment of the Local Government Operation Act (LGOA) in 2017, Nepal laid a robust legal foundation for participatory governance at the grassroots level. This research explores how deliberative decision-making processes are implemented in practice and evaluates the extent to which local governments fulfill their constitutional commitments to inclusiveness and accountability. Adopting a mixed-methods approach, the study integrates questionnaire surveys, qualitative interviews and observations, collecting data from 511 respondents, including elected representatives, administrative staff, and service recipients. The findings indicate that, although legal provisions promote deliberative governance, practical implementation is often constrained by political dominance, procedural rigidity, and limited stakeholder participation. Quantitative findings indicate that approximately 32 percent of key stakeholders (elected representatives and staff) express satisfaction with the deliberative culture of the local executive, while the remainders are neutral or dissatisfied. In contrast, qualitative insights highlight challenges, including the dominance of the ruling party and the influence of individual authority (mayor/chairperson), which impact the decision-making process in local governance. The results indicate a substantial connection between deliberative mechanisms, such as the holding of regular executive meetings, and the transparency in decision-making, which significantly aids in managing citizen grievances. Furthermore, participatory monitoring practices are often merely symbolic, characterized by tokenism, and are not well comprehended by the citizens. The research indicates that deliberative democracy within Nepal’s local governance is still in a nascent stage. To unlock its full potential, it is essential to strengthen institutional capacity, promote civic awareness, ensure inclusive participation, and reinforce regulative mechanisms. Addressing these deficiencies is crucial for embedding substantive deliberative practices into Nepal's decentralized governance framework.